Збереження української нематеріальної культурної спадщини у XXI столітті - Новіков, М. А.; Сергієва, А. В. (ХНУРЕ, 2025)
The importance of Ukrainian historical heritage for the future of the nation. The importance of restoring Ukrainian culture after the end of the war.
Keywords: культурна спадщина; Ukrainian historical heritage